Cechy informacji dostępnych w Internecie - Pondel, Jolanta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
This article presents features of Internet information an important and current source for enterprises wanting to take advantage of this database on today's competitive markets. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 364-372